Challenges and Opportunities of Implementing Open Access Policies - Mensah, Kwame (African Journal of Information and Knowledge Management, 2024)
Purpose: The aim of the study was to investigate the challenges and opportunities of implementing open access policies in African universities. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The implementation of open access policies in African universities faces significant challenges due to limited infrastructure, funding constraints, and inadequate institutional support. However, these challenges also present opportunities for collaboration, capacity building, and leveraging existing networks to enhance access to scholarly research. By overcoming these barriers through strategic partnerships and targeted investments, African universities can foster greater knowledge dissemination, innovation, and socio-economic development across the continent. Unique Contribution to Theory, Practice and Policy: Institutional theory, diffusion of innovation theory& resource dependency theory may be used to anchor future studies on the challenges and opportunities of implementing open access policies in African universities. Implementing open access policies in African universities encourages innovation in knowledge management practices, including the development of institutional repositories, metadata standards, and digital preservation strategies. African universities' implementation of open access policies can influence national and regional policy frameworks related to scholarly communication, research funding, and copyright reform.